Interpreting Hadith through Hadith: Its Concept and Applications (Islamic Sciences Journal, 2026)
The present study seeks to shed light on one of the important topics in the sciences of Hadith, namely the interpretation of Hadith through Hadith. This issue has not received extensive independent study compared to other topics, such as linguistic analysis or the interpretation of Hadith through the Qur’an. The research aims to clarify the concept of interpreting Hadith by Hadith, with a focus on the significance of this methodology in understanding Prophetic traditions. It also reviews practical applications of interpreting Hadith through other Hadiths as found in the books of Sunnah. Based on the nature of the adopted methodology, the study is divided into an introduction, four main sections, and a conclusion presenting the most important findings, which affirm the status and importance of interpreting Hadith through Hadith, along with a recommendation for conducting further studies that address this type of interpretation.
Keywords: Interpretation, Hadith, Concept of Hadith, Applications of Hadith